Filenchus flagellicaudatus n. sp. and Lelenchus schmitti n. sp. (Nemata: Tylenchidae) from Molokai, Hawaii - Bernard, E. C. (Society of Nematologists, 2005)
Filenchus flagellicaudatus n. sp. and Lelenchus schmitti n. sp. are described from Pepe'opae bog on Molokai, Hawaii. Filenchus flagellicaudatus n. sp. is distinguished from all other Filenchus spp. by stylet length (10 µm), robust metacorpus, elongated basal bulb, and extraordinarily long, whip-like tail (c = 2.6, c' = 31.8). Lelenchus schmitti n. sp. differs from other Lelenchus spp. by its shorter body length, weak dorso-ventral compression of the head region, and a more posterior vulva (V = 49-52). The spacious amphid pocket is introduced as a useful character for the differentiation of Lelenchus spp. from other Tylenchidae.